Paket Edukasi Kelompok dan Peran Model Menurunkan Tingkat Isolasi Sosial Pasien HIV/AIDS - Sarwan Sarwan; Busjra M. Nur; Rohman Azzam (Jurnal Keperawatan Silampari, 2019)
The purpose of this study is to identify the effect of group education packages and the role of the model in reducing the social isolation scores of PLWHA in Tangerang District General Hospital. This type of quantitative research is quasi-experimental, pre-test and post-test with control group design. The results of the dependent t-test obtained a mean score of social isolation before the intervention 57.78 and after the intervention 54.44 (p value 0.00 or p <0.05). The conclusion of the study is the effect of group education packages and the role of the model on the reduction of social isolation scores in PLWHA in Tangerang District General Hospital. Implementation of group education and role models need to be done to PLWHA to prevent social isolation, both routinely and gradually and controlled by health workers as educators. Keywords: Social Isolation, PLWHA, Group Education Package, Role of the Model